2000
DOI: 10.1095/biolreprod63.5.1285
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase in the Rat Testis: Evidence for Potential Roles in Both Normal Function and Inflammation-Mediated Infertility1

Abstract: In vitro data have indicated that nitric oxide (NO) inhibits Leydig cell testosterone production, suggesting that NO may play a role in the suppression of steroidogenesis and spermatogenic function during inflammation. Consequently, we investigated expression of the inflammation-inducible isoform of NO synthase (iNOS) in the inflamed adult rat testis and the ability of a broad-spectrum inhibitor of NO production, L-nitro-L-arginine methyl ester, to prevent Leydig cell dysfunction during inflammation. Unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
122
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 37 publications
10
122
0
Order By: Relevance
“…In addition, it has been reported that normal human spermatozoa exhibit eNOS immunostaining that correlates with sperm motility [16], and nNOS immunoreactivity has also been detected in normal rat epididymis [8]. The finding that iNOS was expressed in normal tissue as well as inflamed tissue in the rat testis suggests a unique role for NOS in the male reproductive organs [17].…”
mentioning
confidence: 95%
“…In addition, it has been reported that normal human spermatozoa exhibit eNOS immunostaining that correlates with sperm motility [16], and nNOS immunoreactivity has also been detected in normal rat epididymis [8]. The finding that iNOS was expressed in normal tissue as well as inflamed tissue in the rat testis suggests a unique role for NOS in the male reproductive organs [17].…”
mentioning
confidence: 95%
“…More recently, we have proposed an alternative hypothesis that inflammatory responses in the testis are modified by deviation from the production of key proinflammatory cytokines, such as interleukin (IL)-1␤ and tumor necrosis factor (TNF)-␣, toward immunoregulatory, immunosuppressive, or anti-inflammatory cytokine production (27). This possibility was first suggested by observations that isolated rat testicular macrophages have a reduced capacity to produce IL-1␤ and TNF-␣ in vitro compared with macrophages from other tissues (25,32,33) and exhibit immunosuppressive characteristics in vivo (3,48).…”
mentioning
confidence: 99%
“…The aim of the present study was to examine both proinflammatory and regulatory cytokine production profiles in the whole rat testis in vivo by using our well-characterized LPSinduced inflammation model (19,20,48,49). This model mimics the human response to inflammation and infection of the male reproductive tract, leading to suppression of the hypothalamic-pituitary axis, reduction in androgen production by the Leydig cells, and disruption of the developing germ cells that correlates with the severity of the inflammation (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three additional activin-related p subunits (PC and /3E in mammals and PD in Xenopus laevis) also have been identified but do not appear to play a role in FSH regulation (Hotten er al, 1995;Oda et al, 1995;Fang et al, 1996Fang et al, ,1997Loveland ef al, 1996;Schmitt et al, 1996;O'Bryan et al, 2000;Lau et al, 2000). To date, only one a subunit has been reported.…”
mentioning
confidence: 99%